Role of Soil Moisture and Temperature on Development of Fusarium Wilt in Cucumber - Sharma, Deepika; Shukla, Arti; Gupta, Meenu (International Journal of Economic Plants, 2023)
The research experiment was conducted during the June to August of 2018 under green-house condition at the Experimental farm, Department of Plant Pathology, Dr YS Parmar University of Horticulture and Forestry, Nauni Solan, Himachal Pradesh, India. Mass culture of the pathogenic fungus, Fusarium oxysporum prepared on the corn sand meal medium were inoculated into the sterilized soil (7 cm diameter) in controlled conditions. Sterilized distilled water was sprinkled onto the inoculated soil followed by covering them pots with polythene sheet for about one week for build-up of inoculum. Different moisture and temperature regimes were tested for disease development. Results obtained from the experiments revealed that maximum disease incidence was observed at a soil moisture level of 45% however, no disease was observed at 15% soil moisture regime. Disease development was observed at all the temperature regimes tested except at 15oC where no disease progression was observed even after 21 days of inoculation. Maximum disease incidence (%) was recorded at 25oC temperature. Thus, the present studies indicated that extreme temperature and moisture levels were not found to be favourable for the development of the Fusarium wilt disease in cucumber as disease was observed at optimum environmental conditions of the Fusarium wilt disease in cucumber as disease was observed at optimum environmental conditions.